‘More than a pill’: a qualitative co-exploration of the things that matter in young women's stories of adherence to antiretroviral treatment in South Africa - Lynn Hendricks; Taryn Young; Robin Julies; Rizqah Dollie; Dollie Reshaan; Karin Hannes (Research Involvement and Engagement)
Abstract Background Young women living with perinatal infections of the Human Immunodeficiency Virus (YWLPHIV) in low- and middle-income countries are more likely to be challenged by social and health inequities, which can make adherence to life-long treatment difficult. We aimed to learn more about how YWLPHIV in Cape Town negotiated their adherence to antiretroviral treatment (ART) within their material environments. This study is one of the first to go beyond barriers and facilitators to adherence for people living with HIV to explore the role of the material environment in depth. Methods We adopted a multisensory arts-based community participatory approach and used visual and digital mediums for data-collection and analytical purposes. In our previous work, we identified a gap in the role of the material environment in ART adherence and proposed the Adherence Assemblage model grounded in critical phenomenology, which integrates biological, psychological, social, health system, political, natural, and material dimensions. This study co-explores non-living 'things'—such as bedrooms, doctor’s offices, pill containers, and condoms—that shape young women's adherence to ART in South Africa. The co-research team consisted of three academics, seven YWLPHIV (although they approved the study they could not be named as authors to protect their identities), one counsellor and two visual ethnographers. Data analysis was an iterative process with the co-research team. At first, we would reflect and journal the main insights individually, and then in joint meetings, we shared them. Together, we identified the main storylines and then created collaborative artworks we called, synthesis creations, in response. We operationalised this as a type of creative work that combines and integrates ideas or elements from multiple sources. It typically involves a process of synthesis, in which different pieces of information or artistic materials are brought together and recombined to form a new whole. Results We co-creatively synthesised our findings into one research documentary and five co-creative artworks. We synthesised four storylines: ‘living with a (un)exposed HIV secret’, ‘multisensory experience of adherence’, ‘things that matter in adherence’, and ‘engaging spaces and places. Things such as the pill itself were perceived as triggers for associated memories and evoked emotional responses, impacting the adherence behaviours of YWLPHIV. At times, non-adherence was described as an act of control, with young women narrated an experience of power by rejecting the pills. Besides the more obvious lines of argument on power dynamics, the findings suggest that materiality influences adherence too. However, it is seldom used as an analytical concept to investigate challenges related to ART. Conclusions In conclusion, understanding the material environment's role in adherence is crucial for developing more effective support systems for YWLPHIV. Further research that prioritises the specific needs of YWLPHIV emotional, cognitive, and psychosocial development, while paying attention to the material environment is needed.